Evaluación y entrenamiento de la toma de perspectiva: una propuesta analítica funcional (2010)
According to previous research, perspective-taking can't be easily developed before ages of four years old. Nevertheless, that studies used protocols based on hypothetical situations with a high level of abstraction and, additionally, with a limited number of examples. For this reason, a training protocol for perspective taking, based on real situations was developed. The protocol used a multiple exemplar training, and feedback was provided when was needed. Deictic frames was keeped as a constant (I-YOU, HERE-THERE and NOW-THEN, simple and reversed). An intrasubject ABA design was used in this research. It was obtained that the protocol was effective to develop the abilities of perspective taking in a girl of 3 years and 7 months old. She didn't show the abilities at the first measurement. Also the data of the number of sessions required for training each frame, and their complexity are analyzed under the light of previous research.